Adapting SHIVs In Vivo Selects for Envelope-Mediated Interferon-α Resistance. - David F Boyd; Amit Sharma; Daryl Humes; Cecilia Cheng-Mayer; Julie Overbaugh (PLoS Pathogens, 2016)
Lentiviruses are able to establish persistent infection in their respective hosts despite a potent type-I interferon (IFN-I) response following transmission. A number of IFN-I-induced host factors that are able to inhibit lentiviral replication in vitro have been identified, and these studies suggest a role for IFN-induced factors as barriers to cross-species transmission. However, the ability of these factors to inhibit viral replication in vivo has not been well characterized, nor have the viral determinants that contribute to evasion or antagonism of the host IFN-I response. In this study, we hypothesized that the host IFN-I response serves as a strong selective pressure in the context of SIV/HIV chimeric virus (SHIV) infection of macaques and sought to identify the viral determinants that contribute to IFN-I resistance. We assessed the ability of SHIVs encoding HIV-1 sequences adapted by serial passage in macaques versus SHIVs encoding HIV sequences isolated directly from infected individuals to replicate in the presence of IFNα in macaque lymphocytes. We demonstrate that passage in macaques selects for IFNα resistant viruses that have higher replication kinetics and increased envelope content. SHIVs that encode HIV-1 sequences derived directly from infected humans were sensitive to IFNα -induced inhibition whereas SHIVs obtained after passage in macaques were not. This evolutionary process was directly observed in viruses that were serially passaged during the first few months of infection-a time when the IFNα response is high. Differences in IFNα sensitivity mapped to HIV-1 envelope and were associated with increased envelope levels despite similar mRNA expression, suggesting a post-transcriptional mechanism. These studies highlight critical differences in IFNα sensitivity between HIV-1 sequences in infected people and those used in SHIV models.